2019
DOI: 10.1002/rmv.2045
|View full text |Cite
|
Sign up to set email alerts
|

Role of iron in cancer development by viruses

Abstract: Increased levels of iron in body are attributed to higher cancer risk. Given the fact that 16% of all human cancers are caused by viral infections, iron is suggested to play an important role in carcinogenesis particularly those induced by viral infections. The present study provides an updated summary of the literature and the plausible mechanisms of iron involvement in cancer development by viruses. Our understanding about the interplay between viral infections and iron in different settings particularly can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Ferroptosis is a newly found programmed cell death that relies on iron ion that can promote lipid peroxidation, which is different with apoptosis or necrosis [ 17 ]. The former researches have explored that it is common that high levels of iron are related in a variety of cancer cells rather than in normal cells [ 49 53 ]. Moreover, cell death, especially ferroptosis, is critical for glioma development, and it affects pathological classification and sensitivity to chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a newly found programmed cell death that relies on iron ion that can promote lipid peroxidation, which is different with apoptosis or necrosis [ 17 ]. The former researches have explored that it is common that high levels of iron are related in a variety of cancer cells rather than in normal cells [ 49 53 ]. Moreover, cell death, especially ferroptosis, is critical for glioma development, and it affects pathological classification and sensitivity to chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cells undergoing ferroptosis gain a round shape before death with its distinctive feature, the smaller mitochondria, and increased mitochondrial membrane density. Previously, many pieces of researches have revealed that cancer cells in several cancers e.g., ovarian, lung, and breast cancers have high levels of iron relative to normal cells [ 40 45 ]. Moreover, it is reported that salinomycin can kill cancer stem cells by sequestering iron in lysosomes causing lysosomal membrane permeabilization and ferroptosis, suggesting that therapies targeting ferroptosis might be a possible strategy for cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%